1998
DOI: 10.1182/blood.v91.6.1987
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Regulates Plasminogen Binding and Activation

Abstract: Tissue factor (TF) has been implicated in several important biologic processes, including fibrin formation, atherogenesis, angiogenesis, and tumor cell migration. In that plasminogen activators have been implicated in the same processes, the potential for interactions between TF and the plasminogen activator system was examined. Plasminogen was found to bind directly to the extracellular domain of TF apoprotein (amino acids 1-219) as determined by optical biosensor interaction analysis. A fragment of plasminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Surface receptors that bind glu-plasminogen in a lysine-dependent manner may be classified into two classes. Class 1 binding proteins possess a pre-existing C- 1 Alpha-enolase (81) Intracellular glycolytic enzyme U937 (81) Rat neuronal cells (99) No 1.9* (95) 1.4* (98) 1.0** (46) Cytokeratin 8 (83) Intermediate filament Hepatocytes and MCF-7 cells (83) No 0.16* TIP4a (84) Nuclear ATPase and DNA helicase activity ND 5 No 0.57* 2 Actin (85) Microfilament Endothelial cells (97) MCF-7 and MDA-MB-231 cells (62) No ND Amphoterin (86) Multiple biological functions associated with nervous system Neuronal cells (86) yes ND Annexin II (87) Ca ++ /phospholipid binding protein Endothelial cells (87) Yes 0.16* (88) Glycoprotein IIIb/IIa (78) integrin Platelets (78) Synovial fibroblasts complexed with alpha2macroglobulin (89) Yes ND GP330 (90) Autoantigen associated with Heymann nephritis glomerular epithelial cells (90) Yes~0.25* Tetranectin (92,93) c-type lectin Colocalised with plasminogen in ECM of colonic tumor (103) , melanoma tissue (57) Yes 0.5* Extracellular domain of tissue factor apoprotein (94) Integral membrane glycoprotein initiates extrinsic pathway of coagulation Colocalised with plasminogen in luminal epithelial and smooth muscle cells within a human atherosclerotic plaque (94) Yes 0.1 and 2**…”
Section: Multiple Distinct Proteins May Act As Plasminogen Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Surface receptors that bind glu-plasminogen in a lysine-dependent manner may be classified into two classes. Class 1 binding proteins possess a pre-existing C- 1 Alpha-enolase (81) Intracellular glycolytic enzyme U937 (81) Rat neuronal cells (99) No 1.9* (95) 1.4* (98) 1.0** (46) Cytokeratin 8 (83) Intermediate filament Hepatocytes and MCF-7 cells (83) No 0.16* TIP4a (84) Nuclear ATPase and DNA helicase activity ND 5 No 0.57* 2 Actin (85) Microfilament Endothelial cells (97) MCF-7 and MDA-MB-231 cells (62) No ND Amphoterin (86) Multiple biological functions associated with nervous system Neuronal cells (86) yes ND Annexin II (87) Ca ++ /phospholipid binding protein Endothelial cells (87) Yes 0.16* (88) Glycoprotein IIIb/IIa (78) integrin Platelets (78) Synovial fibroblasts complexed with alpha2macroglobulin (89) Yes ND GP330 (90) Autoantigen associated with Heymann nephritis glomerular epithelial cells (90) Yes~0.25* Tetranectin (92,93) c-type lectin Colocalised with plasminogen in ECM of colonic tumor (103) , melanoma tissue (57) Yes 0.5* Extracellular domain of tissue factor apoprotein (94) Integral membrane glycoprotein initiates extrinsic pathway of coagulation Colocalised with plasminogen in luminal epithelial and smooth muscle cells within a human atherosclerotic plaque (94) Yes 0.1 and 2**…”
Section: Multiple Distinct Proteins May Act As Plasminogen Receptorsmentioning
confidence: 99%
“…A bona-fide receptor must be shown to be at the cell-surface orientated towards the extracellular environment where it can bind plasminogen so as to be efficiently activated. Other than immunocytochemical localization, a definitive study showed that CHO cells engineered to express cell surface tissue factor bound 70% more plasminogen than control CHO cell lines (93). Furthermore, care must be taken to ensure that receptor isolation procedures, especially when using whole cell lysates, do not simply result in the isolation of intracellular proteins that fortuitously bind plasminogen.…”
Section: A Bona-fide Receptor Must Be Shown To Be At the Cell-surfacementioning
confidence: 99%
See 2 more Smart Citations
“…These include tissue factor pathway inhibitor (TFPI), plasminogen, and filamin. 49,[51][52][53] TF procoagulant activity is inhibited by TFPI when it is in complex with FVIIa and FXa. 45 The TF cytoplasmic domain binds filamin, which supports TF-dependent adhesion contacts associated with cytoskeletal reorganization.…”
Section: Tissue Factormentioning
confidence: 99%